Increased Axon Initial Segment Length Results in Increased Na+ Currents in Spinal Motoneurones at Symptom Onset in the G127X SOD1 Mouse Model of Amyotrophic Lateral Sclerosis. (1st August 2021) - Jørgensen, H.S.; Jensen, D.B.; Dimintiyanova, K.P.; Bonnevie, V.S.; Hedegaard, A.; Lehnhoff, J.; Moldovan, M.; Grondahl, L.; Meehan, C.F.
Highlights: In vivo electrophysiological recordings were made in symptomatic G127X SOD1 mice. There were no deficits in repetitive firing in motoneurones in G127X mice. Increased persistent inward currents were still present in the symptomatic mice. Results suggest increases in Na + currents at axon initial segments (AISs). Immunohistochemistry showed that motoneurone AISs were longer and thinner. Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease preferentially affecting motoneurones. Transgenic mouse models have been used to investigate the role of abnormal motoneurone excitability in this disease. Whilst an increased excitability has repeatedly been demonstrated in vitro in neonatal and embryonic preparations from SOD1 mouse models, the results from the only studies to record in vivo from spinal motoneurones in adult SOD1 models have produced conflicting findings. Deficits in repetitive firing have been reported in G93A SOD1 (high copy number) mice but not in presymptomatic G127X SOD1 mice despite shorter motoneurone axon initial segments (AISs) in these mice. These discrepancies may be due to the earlier disease onset and prolonged disease progression in G93A SOD1 mice with recordings potentially performed at a later sub-clinical stage of the disease in this mouse. To test this, and to explore how the evolution of excitability changes with symptom onset we performed in vivo intracellular recording and AIS labelling in G127X SOD1 mice immediately after symptom onset. No reductions in repetitive firing were observed showing that this is not a common feature across all ALS models. Immunohistochemistry for the Na + channel Nav1.6 showed that motoneurone AISs increase in length in G127X SOD1 mice at symptom onset. Consistent with this, the rate of rise of AIS components of antidromic action potentials were significantly faster confirming that this increase in length represents an increase in AIS Na + channels occurring at symptom onset in this model.